Pengelolaan Limbah Rumah Tangga Menjadi Lilin Aromaterapi dari Minyak Jelantah di SDN 41 Ampenan - Fauzi, Asri; Sopani, Elza Maulia; Putri, Ersa Anugraheni; Aisy, Nurul Raodatul; Nurul Saudah; Pathiah (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Household waste, especially used cooking oil, has a negative impact on the environment and health if not managed properly. Used cooking oil is often disposed of carelessly, causing soil, water, and air pollution. To overcome this problem, a program is implemented with the aim of reducing used cooking oil waste and creating student awareness about waste management. This program utilizes used cooking oil into aromatherapy candles that are useful and have a selling value. The socialization and practice of making aromatherapy candles was carried out by students in grades 4 and 5 of SDN 41 Ampenan, accompanied by Teaching Assistance Students. This activity involves group division, material collection, and the process of making candles from used cooking oil with additional natural aromas such as pandan leaves, oranges, jasmine tea, coffee, and lemongrass. The practice of making aromatherapy candles takes place from May 22 to May 29, 2024. The results of this activity show that aromatherapy candles made have health benefits and can reduce B3 waste in households. Students also gain knowledge about the negative effects of used cooking oil if used continuously and the importance of recycling. This practice has succeeded in improving students' skills and creativity in managing waste and providing potential entrepreneurial ideas. So, this activity not only succeeded in reducing used cooking oil waste but also increased students' awareness of the importance of preserving the environment from an early age.